2022
DOI: 10.1038/s41598-022-09784-8
|View full text |Cite
|
Sign up to set email alerts
|

Elements of chronic disease management service system: an empirical study from large hospitals in China

Abstract: At present, more patients suffer from multiple chronic diseases. However, the hospital's existing chronic disease management is carried out according to the department. This means that a patient needs to go to more than one department for a chronic disease treatment. Therefore, this study proposes 6 dimensions (organizational management, medical service support, medical service, community alliance, self-management support, management information system) and 36 questions, to help evaluate the current chronic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…These results vary from the study conducted in Yemen, where they reported having a Pharm.D degree and dealing with more than 75 prescriptions per day was associated with high knowledge scores among community pharmacists ( Al-Ashwal et al, 2022 ). The huge volume of prescriptions preferably for CVD in the hospital pharmacy is might be due to the requirement of periodic follow up and specialized care for chronic diseases ( Zhao et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results vary from the study conducted in Yemen, where they reported having a Pharm.D degree and dealing with more than 75 prescriptions per day was associated with high knowledge scores among community pharmacists ( Al-Ashwal et al, 2022 ). The huge volume of prescriptions preferably for CVD in the hospital pharmacy is might be due to the requirement of periodic follow up and specialized care for chronic diseases ( Zhao et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…These geriatric illnesses pose a significant threat to the health of older adults and are likely to result in death [ 10 ]. Furthermore, the onset of these diseases can lead to a rapid decline in both physical and economic quality of life, having a profound impact not only on the individuals but also their families [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the development of medical technology and disease management systems, referring to the relatively complete process from preliminary diagnosis to clinical decision-making to personalized treatment ( 5 ), mortality caused by chronic diseases has decreased in high-income countries, and the speed is significantly faster than that for low- and middle-income countries ( 6 ). Simultaneously, there is evidence showing that, in low-income countries, the risk of death from non-infectious chronic diseases is twice that in high-income countries ( 7 ).…”
Section: Introductionmentioning
confidence: 99%